TTTIs:A Future Vision - Agrawal, D. P.; Raina, K. B. (Journal of Engineering Education Transformations, 1998)
TECHNICAL EDUCATION IN INDIA: Technical Education in India has a history of over 150 years. The development of technician education before independence was slow and unplanned and was fashioned on the western on the western models. During the post independence period, India witnessed considerable changes in the objectives and pattern of technical education and realization that technical education is an essential prerequisite for economic development of the country and for improving the quality of life of its people.